ANALISIS PRODUCTION PLANNING AND CONTROL PADA PROSES PERBAIKAN KOMPONEN PESAWAT EMERGENCY POWER SUPPLY DI PT DIRGANTARA INDONESIA - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Rafika Ratik Srimurni, Rafika Ratik Srimurni; Sonya Farida, Sonya Farida (Fakultas Teknik, 2024)
In the context of the MROC Department, the Production, Planning and Control Division is responsible for coordinating and accelerating the flow of work and materials within or between departments of a company according to the production schedule. Internship activities will be carried out on 3 October 2023 / 29 December 2023. Data collection is carried out by means of observation, interviews and literacy studies. This internship report uses additive decomposition methods and BEP analysis in the data processing process. The production, planning and control process flow for the emergency power supply aircraft component repair process starts with Receive Work Breakdown Structure (WBS) from OM to Send Serviceable Component and Associated Document (ARC, Repair Report). The SAP system in the production, planning and control process functions to check stock, create OP (Order Processing), and update OP (Order Processing). The quality standards used by the Sub.Directorate Aircraft Services are ISO 9100:2015 and AS 9110 C. The operations management system implemented by PPC-MROC is a JIT (Just in Time) system. The application of QMS in the PPC MROC field lies in the documents used to record all information related to components including WBS (Work Breakdown Structure), Farm-Out, Stripping Report, Repair Report, Worksheet, Repair Completed Information, and ARC. Predictions for the number of emergency power supply aircraft component repairs using the additive decomposition model for the period 2024, quarter 1 is 11, quarter 2 is 7, the 3rd quarter is 10, and the 4th quarter is 15. The Production Planning and Control Component Shop sector has a sequential independence relationship with the MROC Department. The BEP analysis result is 1, meaning that the process of repairing emergency power supply components is feasible.